Le blasphème du péché au crime - Dierkens, Alain (Problèmes d'histoire des religions, 2012)
Considered an attack on the very foundation of the social order and public morality, blasphemy has been and is still repressed as such. Recently, however, certain international events and identity claims have raised new questions about the forms, the nature and the lawfulness of speeches and images showing disrespect for religions, even in the satirical mode. By examining the contemporary manifestations of what is considered outrageous by religions, but also by considering the history and anthropology of the "unholy word" and its reception, the studies collected in this book provide a better understanding of how this category of religious and legal discourse has been constructed over time, with the aim of suppressing certain forms of protest against established religions and their symbols. For the repression of blasphemy shows the complexity of its social and judicial management, at the heart of the tension between freedom of conscience ("slanderer" and "defamation"), freedom of expression and censorship.